If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (T + -7)(6t + -7) = 0 Reorder the terms: (-7 + T)(6t + -7) = 0 Reorder the terms: (-7 + T)(-7 + 6t) = 0 Multiply (-7 + T) * (-7 + 6t) (-7(-7 + 6t) + T(-7 + 6t)) = 0 ((-7 * -7 + 6t * -7) + T(-7 + 6t)) = 0 ((49 + -42t) + T(-7 + 6t)) = 0 (49 + -42t + (-7 * T + 6t * T)) = 0 (49 + -42t + (-7T + 6tT)) = 0 Reorder the terms: (49 + -7T + -42t + 6tT) = 0 (49 + -7T + -42t + 6tT) = 0 Solving 49 + -7T + -42t + 6tT = 0 Solving for variable 'T'. Move all terms containing T to the left, all other terms to the right. Add '-49' to each side of the equation. 49 + -7T + -42t + -49 + 6tT = 0 + -49 Reorder the terms: 49 + -49 + -7T + -42t + 6tT = 0 + -49 Combine like terms: 49 + -49 = 0 0 + -7T + -42t + 6tT = 0 + -49 -7T + -42t + 6tT = 0 + -49 Combine like terms: 0 + -49 = -49 -7T + -42t + 6tT = -49 Add '42t' to each side of the equation. -7T + -42t + 42t + 6tT = -49 + 42t Combine like terms: -42t + 42t = 0 -7T + 0 + 6tT = -49 + 42t -7T + 6tT = -49 + 42t Reorder the terms: 49 + -7T + -42t + 6tT = -49 + 42t + 49 + -42t Reorder the terms: 49 + -7T + -42t + 6tT = -49 + 49 + 42t + -42t Combine like terms: -49 + 49 = 0 49 + -7T + -42t + 6tT = 0 + 42t + -42t 49 + -7T + -42t + 6tT = 42t + -42t Combine like terms: 42t + -42t = 0 49 + -7T + -42t + 6tT = 0 The solution to this equation could not be determined.
| -6(1+r)-8r=92 | | 2(3x+4)=5(x-1)+x+13 | | 2x+9=2x+22 | | J=z-a/x | | 5t+4=1t-2 | | J(8j-7)=0 | | -3x+-6= | | 6(2a+10)=5a+5 | | 21-2x=43-5x | | 6d-2= | | (x)/(2)-1=2-x | | ×/3=11 | | (-4.3)-z=11 | | 2x+2=4+6x-54 | | 47-7x=5x-20 | | (S+5)(8s+9)=0 | | 7.9x-17.9=29.5 | | -12(x+4)=-3(x+6)+x-30 | | 0.5(4x-1)=4(3+x) | | 2a+28=4a-4 | | 144-5x=171-8x | | 3(x+3)-10=32 | | 6x+5+3x=136 | | 12-x=36 | | (7n-3)(6n-7)=0 | | h=(-16)t^2+800(t)+125 | | sin(5t)-cos(5t)=0 | | 6a-5= | | (8z-1)(z+3)=0 | | 130x+46=7 | | H(2h+9)=0 | | 4(6+4n)=120 |